Análise das emissões atmosféricas por veículos automotores em Natal-RN - Brito, Hermínio Pereira de (2005)
The fast urban occupation of Brazil, mainly from the last decade of 50, a sensible degradation of the quality of the air generated mainly for the activities was verified human beings associates to industrialization. From the past years, the situation has gotten worst in function of the increment of the fleet of vehicles in circulation in the great cities. Being these, in the city of Natal-RN, the ones that offer the biggest contributions to the atmospheric pollution. For atmospheric air to be a finite natural resources, indispensable and essential to the maintenance of the life in the land, is necessary to the implementation of action to improve its quality and to protect the health of the population. With the objective to study relative aspects to the characteristics of vehicles in use, the present study it searchs to analyze the levels of emissions of gases generated for vehicles converted bi-fuels into the modalities: natural gas (GNV), gasoline and alcohol, inspected for ends of register and together licensing to the State Department of Transit. One used the data gotten from inspections carried through for the company System Specialized in Inspection To propagate, in the city of the Natal-RN, capital of the State of Rio Grande do Norte, between 14 of November of 2003 and 30 of December of 2004. The analyzed parameters are established in the resolution nº 07/93 CONAMA. Of a total of 1.517 inspected vehicles, a average of 15,2% of failed was gotten, or either, that they emit levels of pollution above of the limits established for the legislation, below of the national average that is of 20,0%. The analysis of the data discloses that 7.3% of the fleet are converted the GNV; the growth of vehicles converted the GNV into the city is gradual, with a average of increment in last the 4 years of 23,3%; it has a vehicle predominance that has as combustible original to the gasoline (88,2%); the inspected fleet has average age of 8 years of use, considered young for the Brazilian standards, except for the moved one to the alcohol (average of use of 15 years). Moreover, the type of fuel is not the main parameter to define the indices of emissions; the age of the fleet is the parameter most important when emission is analyzed to propagate; the gas that more generates failed in the inspections is the corrected carbon monoxide; the vehicles generate higher indices of emissions in idling for all the fuels; the presence of the catalyser was not reflected, as it expected, in the reduction of emissions of gases toxic, however when analyzed according to year of manufacture, it was observed that for the vehicles manufactured between 1997 and 2004, reduction of 46,0% in the failed of the vehicles equipped with catalyser was gotten. In conclusion, the fleet of the studied sample, in average terms, takes care of to the requirements of Resolution CONAMA nº 07/93. The results gotten for the present study can subsidize action of public administrations that aim at to the improvement and the maintenance of the quality of air in the city of Natal-RN, as, for example, to implant a net of monitoramento of the quality of air